2018
DOI: 10.1099/mic.0.000683
|View full text |Cite
|
Sign up to set email alerts
|

A novel regulatory factor affecting the transcription of methionine biosynthesis genes in Escherichia coli experiencing sustained nitrogen starvation

Abstract: The initial adaptive transcriptional response to nitrogen (N) starvation in Escherichia coli involves large-scale alterations to the transcriptome mediated by the transcriptional activator, NtrC. One of these NtrC-activated genes is yeaG, which encodes a conserved bacterial kinase. Although it is known that YeaG is required for optimal survival under sustained N starvation, the molecular basis by which YeaG benefits N starved E. coli remains elusive. By combining transcriptomics with targeted metabolomics anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Therefore, an exponentially growing batch culture of E. coli rapidly attenuates growth upon N run-out ( 9 11 ). The initial adaptive response to N run-out, the N regulation (Ntr) stress response, results in the large-scale and multilevel reprogramming of the transcriptome, involving ∼40% of all E. coli genes, to allow E. coli to adjust to N starvation ( 12 14 ). Since E. coli perceives N run-out as a decrease in the internal concentration of glutamine, the genes expressed as part of the Ntr response are predominantly involved in the transport and assimilation of nitrogenous compounds into glutamine or glutamate, yielding these catabolically or sparing the requirement for them in cellular processes ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an exponentially growing batch culture of E. coli rapidly attenuates growth upon N run-out ( 9 11 ). The initial adaptive response to N run-out, the N regulation (Ntr) stress response, results in the large-scale and multilevel reprogramming of the transcriptome, involving ∼40% of all E. coli genes, to allow E. coli to adjust to N starvation ( 12 14 ). Since E. coli perceives N run-out as a decrease in the internal concentration of glutamine, the genes expressed as part of the Ntr response are predominantly involved in the transport and assimilation of nitrogenous compounds into glutamine or glutamate, yielding these catabolically or sparing the requirement for them in cellular processes ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Fig. 2E, RpoS is clearly upregulated, and RpoS-dependent gene expression has been demonstrated to be active under our N-starvation conditions (8). Therefore, I decided to determine whether RpoS plays a role in the formation of N-starvation-induced persisters.…”
Section: Resultsmentioning
confidence: 89%
“…The response also induces the further expression of genes to survive N starvation through the action of the dual regulator Nac, the nitrogen accessory control protein (6). Recently, we showed that the least understood NtrC-regulated operon, yeaGH, which encodes a putative serine/ threonine kinase and has a gene of unknown function, promotes the survival of E. coli when faced with sustained N starvation, appearing to act as a molecular brake, dampening the metabolic activity of N-starved E. coli (7,8).…”
mentioning
confidence: 99%
“…We defined differentially expressed genes as those with expression levels changed ≥ 2-fold with a false discovery rate adjusted P-value < 0.05. As previously reported by us and others, the initial transcriptional response to N starvation involves differential expression of 1787 genes primarily required for scavenging and catabolism of alternative N sources (6, 8, 9) and thus, we did not investigate these genes further (Phase A in Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The RNA-seq data set was previously generated and analysed by Switzer et al (8). The analysis of differential gene expression during NAP as well as the statistical analyses were also conducted in the same way as described previously.…”
Section: Methodsmentioning
confidence: 99%